2019
DOI: 10.30659/jdh.v2i1.4149
|View full text |Cite
|
Sign up to set email alerts
|

Constitution and Constitutionalism of Indonesia

Abstract: The term constitution comes from a constituer which means to form, that is , the whole of the rules both written and unwritten which regulate in a binding manner the way a government is held in a society. Constitutionalism in the strict sense is that the administration of the government which islimited by the Constitution, in a broad sense, is a set of political values and aspirations that reflect the desire to protect freedom by carrying out internal and external supervision of government power.There are diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Secondary data consists of tertiary legal materials in the form of legal dictionary books and relevant encyclopedias that are in accordance with the object of research. The data collection method in the form of taking and determining the sample was chosen to be a respondent using a non-random sampling technique 8 . In line with that the data analysis method is intended for sampling not done randomly but by being selected based on certain considerations that are aligned with the research objectives then reduced, categorized and then concluded.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary data consists of tertiary legal materials in the form of legal dictionary books and relevant encyclopedias that are in accordance with the object of research. The data collection method in the form of taking and determining the sample was chosen to be a respondent using a non-random sampling technique 8 . In line with that the data analysis method is intended for sampling not done randomly but by being selected based on certain considerations that are aligned with the research objectives then reduced, categorized and then concluded.…”
Section: Methodsmentioning
confidence: 99%
“…Termination of prosecution for policy reasons, where the prosecutor is allowed to put aside the case even though there is sufficient evidence to be 6 transferred to the court for public interest or individual interests and is based on unwritten law (opportunity principle). Based on article 77 of the Criminal Procedure Code, the Attorney General has the authority to set aside a case, where the action for setting aside a case consists of: 8  Set aside the case on the principle of opportunity, for the following reasons:…”
Section: Application Of Prosecutors' Policy Authority In Terminating ...mentioning
confidence: 99%
“…It is a written constitutional document that represents the political struggle and aspirations of the Indonesian people in the past. (Praptini et al, 2019;Perwira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%